Measurements of Natural and Synthetic Diamond Samples Using Kelvin Probe, Surface Photovoltage and Ambient Pressure Photoemission Techniques. (6th February 2017) - Challinger, Susanna; Baikie, Iain; Birdwell, A. Glen
ABSTRACT: Diamond is a promising wide band-gap semiconductor material for use in devices; therefore a thorough understanding of the surface electronic structure is important. The Kelvin Probe (KP), Surface Photovoltage / Surface Photovoltage Spectroscopy (SPV/SPS) and Ambient Pressure Photoemission Spectroscopy (APS) techniques are commonly applied to traditional and organic semiconductor materials. The application of these techniques to synthetic and natural diamond samples provides some challenges: surface charge on the samples and atypical capacitive interaction with the KP tip. In this study, measurements using a combination of KP, SPV/SPS and APS techniques are taken of samples of natural and synthetic diamond samples to investigate their surface electronic structure and compare their different properties. These techniques are all non-contact and non-destructive. The Fermi Level position of the diamond samples was found to vary, typically between 4.3 – 4.9 eV, depending on the light illumination. For example, when a natural diamond sample was illuminated with 400 nm light from a 150W Quartz Tungsten Halogen light source, there was a surface photovoltage response of ∼250 mV. The oxygen terminated synthetic diamond sample required near continuous illumination at low visible wavelengths in order to retain sufficient conductivity to allow measurement with the Kelvin Probe. By contrast, the natural diamond samples measured showed good conductivity in the layers underneath the top surface. In summary, the KP, SPV/SPS and APS measurement techniques provided some interesting information on the diamond samples and an initial investigation of their surface electronic states is performed.